Self vs. other raters' assessment of emotional intelligence in private and public hospitals: A comparative study - Rateb J. Sweis; Sawsan Aldaod; Niveen M. AlSayyed; Lilana Sukkari (Administrative Sciences, 2022)
This study aims to investigate the levels of emotional intelligence for managers in public and private hospitals in Jordan for the purpose of identifying the relative practice of emotional intelligence dimensions by managers in each sector. The research will also look into the differences (gaps) in self- and other-assessed emotional intelligence for managers in both public and private hospitals. As such, the theoretical importance of this research lies in its ability to contribute to filling the missing gap in the literature while forming the basis for or being the object of reference for any future research in the field. The researchers adopted a quantitative research design. Data were collected using a 360-degree questionnaire, in which managers' self-assessments, and the assessments of two other raters (supervisors, peers, or subordinates), were used to measure the levels of managers' emotional intelligence in both public and private hospitals. A total of 179 managers and 358 raters participated in our study. The results of the study revealed that differences between managers' self-assessments and others' assessments might be an indicator of inflated managers' self-assessments. Differences between managers' self-assessments and others' assessments were larger in public hospitals compared with those in private hospitals. Hence, our study provides valuable recommendations and implications to enhance the practice of emotional intelligence among managers both in public and private hospitals in Jordan.
Keywords: 350; emotional intelligence; private hospitals; public hospitals; raters' assessments; self-assessment